2022
DOI: 10.1177/10790632221127980
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Effect of Post-Release Housing Mobility on Recidivism: Considering Individuals Convicted of Sexual Offenses

Abstract: It is widely understood that stable housing is a key element in the transition from prison to the community. However, many persons under correctional supervision face substantial barriers in securing and maintaining housing, a fact that is heightened among individuals with a sexual offense conviction. Although frequent movement is commonplace among people on parole, it is unclear how housing changes affect recidivism outcomes and whether such mobility uniquely impacts individuals with a sexual offense convicti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 98 publications
0
1
0
Order By: Relevance
“…Some other research has focused more explicitly on postrelease recidivism which reflects offending that occurred once an individual has been released from a community corrections program. These studies have found that postrelease recidivism was correlated with the security level where the individual was incarcerated (Gaes & Camp, 2009), prison misconduct (Cochran et al, 2014), education (Lockwood et al, 2016; Nally et al, 2012; Roessger et al, 2021), employment (Nally et al, 2014; Skardhamar & Telle, 2012), and housing stability (Rydberg et al, 2023). These studies illustrate how factors that influence recidivism transcend community supervision.…”
Section: Measuring Recidivismmentioning
confidence: 99%
“…Some other research has focused more explicitly on postrelease recidivism which reflects offending that occurred once an individual has been released from a community corrections program. These studies have found that postrelease recidivism was correlated with the security level where the individual was incarcerated (Gaes & Camp, 2009), prison misconduct (Cochran et al, 2014), education (Lockwood et al, 2016; Nally et al, 2012; Roessger et al, 2021), employment (Nally et al, 2014; Skardhamar & Telle, 2012), and housing stability (Rydberg et al, 2023). These studies illustrate how factors that influence recidivism transcend community supervision.…”
Section: Measuring Recidivismmentioning
confidence: 99%